miR-224 activates cancer-associated fibroblasts to enhance lung cancer cell migration and invasion by targeting Akirin1 - Seonyeong Oh; Sieun Lee; Inyoung Cheon; Young-Ho Ahn (Scientific Reports)
Abstract Cancer-associated fibroblasts (CAFs) actively contribute to the formation of tumor-supportive microenvironments, thereby promoting cancer progression and impacting therapeutic outcomes. This study utilized global microRNA (miRNA) expression profiling to identify specific miRNAs responsible for reprogramming normal lung fibroblasts (LFs) into CAFs. miR-224 demonstrates increased expression in CAFs, and its levels are elevated in lung tumors compared to those in normal tissues, according to data from public databases. Overexpression of miR-224 in LFs increases the overall expression of CAF activation markers. Furthermore, LFs overexpressing miR-224 enhanced the migration and invasion of lung cancer cells via direct cell-to-cell contact in a co-culture system. In a mouse orthotopic injection model, miR-224 overexpression in LFs increased lung cancer metastasis. Using target prediction tools and subsequent 3′-UTR luciferase assay, Akirin1 was validated as a direct target gene of miR-224. In addition, LFs depleted of Akirin1 by siRNAs stimulated the migration and invasion of lung cancer cells compared to control LFs. Overall, these findings indicate that miR-224 induces CAF activation and promotes the migration and invasion of lung cancer cells by targeting Akirin1 in co-culture systems.